The Effect of Pandemic Movement Restriction Policies on Children's Physical Fitness, Activity, Screen Time, and Sleep - Morrison, Shawnda A.; Meh, Kaja; Sember, Vedrana; Starc, Gregor; Jurak, Gregor (Frontiers in Public Health, 2021)
Background The negative impact of isolation, confinement and physical (in)activity due to pandemic movement restriction has been well documented over the past year, but less is known on the impact of these policies on children’s physical fitness. This study was designed to determine the effects of pandemic movement restriction policies on the 24-hour movement behaviour (24-HMB) of children, and whether any alterations are reflected in worsening physical fitness outcomes determined via direct testing. Methods A two-phase, repeated-measures study with matched controls was conducted. Phase One: N=62 schoolchildren (N=31 female) completed self-assessment questionnaires on 24-HMB in October 2018 (pre-pandemic) and again in April 2020, at the height of movement restrictions enacted in response to the COVID-19 pandemic first wave. Phase Two: physical fitness of the original N=62 children were determined directly pre- and post-isolation using an eight-component standardised fitness test battery and then compared to N=62 unique, control children who were matched for age, sex, school region and fitness centile scores. Results During lockdown (total duration: 63 days), MVPA decreased by ~46 min per day, screen time demonstrated a significant interaction effect, such that kids reported spending less recreational screen time on weekends during lockdown compared to no restriction, and sleep duration was consistently lower during lockdown (95% CI: -104.1 to -45.5 min, p<0.001). No interaction effect was present for direct fitness indicators, including: hand tapping (reaction time), standing broad jump, polygon backward obstacle course (coordination), sit-ups, stand-and-reach, bent-arm hang, 60-m and 600-m run (p≥0.05) although significant main effects are noted for each for both sexes. Conclusion Initial changes in 24-HMB did not translate to reductions in physical fitness indices, likely due to the high initial fitness levels of the children. Further work is needed to confirm whether longer or repeated movement restrictions exacerbate initial negative 24-HMB trends, especially for children who are less fit when restrictions are initiated, prolonged or repeated.